Monitoring quality at scale: implementing quality assurance in a diverse, multicountry HIV program. (July 2015) - Saito, Suzue; Howard, Andrea A.; Chege, Duncan; Ellman, Tanya M.; Ahoua, Laurence; Elul, Batya; Rabkin, Miriam
Abstract : The centrality of quality as a strategy to achieve impact within the U.S. President's Emergency Plan for AIDS Relief (PEPFAR) has been widely recognized. However, monitoring program quality remains a challenge for many HIV programs, particularly those in resource-limited settings, where human resource constraints and weaker health systems can pose formidable barriers to data collection and interpretation. We describe the practicalities of monitoring quality at scale within a very large multicountry PEPFAR-funded program, based largely at health facilities. The key elements include the following: supporting national programs and strategies; developing a conceptual framework and programmatic model to define quality and guide the provision of high-quality services; attending to program context, as well as program outcomes; leveraging existing and routinely collected data whenever possible; developing additional indicators for judicious use in targeted, in-depth assessments; providing hands-on support for data collection and use at the facility, sub-national, and national levels; utilizing web-based databases for data entry, analysis, and dissemination; and multidisciplinary support from a large team of clinical and strategic information advisors.